2005
DOI: 10.1007/s00534-004-0956-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis in which differential diagnosis from gallbladder carcinoma was difficult

Abstract: We report a case of localized primary sclerosing cholangitis (PSC) which was difficult to distinguish from gallbladder carcinoma. A 75-year-old woman with elevated serum bilirubin was hospitalized and underwent endoscopic nasobiliary drainage (ENBD). There was no history of diseases such as gallbladder stone, pancreatitis, or ulcerative colitis. Cholangiography through the ENBD tube showed localized stenosis of the common bile duct; the gallbladder could not be seen. Angiography showed no encasement of the hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In addition, it has also been reported that the prevalence of gallbladder polyps in PSC patients was 4%, and gallbladder neoplasms in PSC are malignant in approximately 40–60% of the cases [4, 5]. Thus, previous reports suggest some correlation among the PSC and UC patients and not only for cholangiocarcinoma but also carcinoma of the gallbladder []. In this report, we demonstrate the clinicopathological features of a mucin‐producing carcinoma of the gallbladder associated with PSC and UC.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, it has also been reported that the prevalence of gallbladder polyps in PSC patients was 4%, and gallbladder neoplasms in PSC are malignant in approximately 40–60% of the cases [4, 5]. Thus, previous reports suggest some correlation among the PSC and UC patients and not only for cholangiocarcinoma but also carcinoma of the gallbladder []. In this report, we demonstrate the clinicopathological features of a mucin‐producing carcinoma of the gallbladder associated with PSC and UC.…”
Section: Introductionsupporting
confidence: 68%
“…Previous reports suggest some correlation among the PSC and UC patients and not only for cholangiocarcinoma but also carcinoma of the gallbladder [4][5][6][7]. Buckles et al Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7 Since the risk of hepatobiliary carcinoma is high in patients with PSC and the differential diagnosis is diffi cult, a cholecystectomy is recommended when a GB mass lesion is detected. 5,8,9 Xanthogranulomatous cholecystitis is a type of chronic cholecystitis characterized by the infi ltration of numerous foamy histiocytes with infl ammatory cells. Bacterial infections, such as Escherichia coli and LPS, and resultant infl ammatory and immunological events are thought to be involved in the pathogenesis of XGC.…”
Section: Discussionmentioning
confidence: 99%
“…This patient died of metastases 6 months after transplant. The incidence of gallbladder carcinoma is increased in PSC patients, and it is often difficult to diagnose early in its development [33]. Another type of malignancy occurred 8 years after initial endoscopic therapy in one of our patients presumably from acquisition of Epstein-Barr virus at the time of transplant [34,35].…”
Section: Patientsmentioning
confidence: 98%